The association of transporter ABCC2 (MRP2) genetic variation and drug-induced hyperbilirubinemia. Issue 2 (4th February 2021) - Huang, Yi-Shin; Chang, Tien-En; Perng, Chin-Lin; Huang, Yi-Hsiang
Abstract : Background: Hyperbilirubinemia is a predictor of severe drug-induced liver injury (DILI). Hepatobiliary ATP-binding cassette (ABC) transporters play an important role in the transportation of many drugs and bilirubin; however, little is known about these transporters and the risk of DILI. The aim of this study was to explore associations between genetic variations in important ABC transporters and susceptibility to DILI, with a particular focus on hyperbilirubinemia. Methods: A total of 200 patients with DILI and 200 healthy controls were enrolled as the training dataset. Another 106 patients with DILI were recruited as the validation dataset. They were genotyped for ABCB11 (BSEP ) rs2287622, ABCB1 (MDR1 ) rs1128503, rs1045642, ABCB4 (MDR3 ) rs2230028, ABCC2 (MRP2 ) rs1885301, rs717620, rs2273697, rs3740066 and rs8187710 using polymerase chain reaction–based TaqMan genotyping assays. Results: There were no statistical differences in any of the nine ABC transporter single nucleotide polymorphisms between the DILI and control groups. However, in the DILI group, the patients with hyperbilirubinemia had a higher frequency of the ABCC2 rs717620 C/T and T/T genotypes than those without hyperbilirubinemia (44.2% vs 20.2%, p = 0.001). After adjusting for other confounding factors, the ABCC2 rs717620 T variant was still associated with an increased risk of hyperbilirubinemia (adjusted odds ratio [OR]: 3.83, 95% confidence interval [CI]: 1.73-8.48, p = 0.001). This association was confirmed by the validation dataset (adjusted OR: 3.92, 95% CI: 1.42-10.81, p = 0.015). We also found that the mortality group had higher frequencies of the ABCC2 (MRP2 ) rs717620 C/T and T/T genotypes than the survival group (50.0% vs 27.9%, p = 0.048). Conclusion: Carriage of the ABCC2 (MRP2 ) rs717620 T variant may increase the risk of hyperbilirubinemia and mortality in patients with DILI. Screening for this variant may help to prevent and mitigate drug-induced hyperbilirubinemia.